Validation of the name Rhododendron xishuiense (Ericaceae) - Tong, Yi-Hua; Yang, Cheng-Hua; Xia, Nian-He (Phytotaxa, 2020)
Rhododendron xishuiense C.H.Yang & C.D.Yang in Yang et al. (2012: 95) was described based on material from Xishui, Guizhou, China. In the protologue, Yang et al. (2012) provided a Latin description and cited two collections, C.H. Yang 5784 with flowers and C.H. Yang 7590 with fruits. Both of the collections were deposited in the herbarium of Guizhou Academy of Forestry (GF). However, no type was indicated in the protologue. According to Art. 40.1 & 40.6 of ICN (Turland et al. 2018), it was invalidly published. Here R. xishuiense is validated by reference to the previously published description (Yang et al. 2012) and by designating the specimen with flowers (C.H. Yang 5784) as its holotype.